A Validated Ultra Performance Liquid Chromatography Method for Quantification of Metformin in Human Plasma - Vycke Yunivita Kusumah Dewi; Atu Purnama Dewi; Budi Setiabudiawan; Edhyana Sahiratmadja; Triana Nurul Meirina; Harold Eka Atmaja; Rovina Ruslami (Chemistry Department, The University of Brawijaya, 2018)
Metformin is oral hypoglycemic or blood sugar-lowering drug which is used for the first- line drug in the treatment of diabetes mellitus type 2. This study presented the validated Ultra Performance Liquid Chromatography UltraViolet (UPLC-UV) method for the determination of metformin in human plasma. Metformin levels were measured using UPLC with a UV detector and liquid-liquid extraction method. Separation was carried out on an Acquity UPLC HSS T3 100mm × 2.1mm i.d. column (1.8μm particle size) using gradient elution of acetonitrile and phosphate buffer 0.02 M (0.6 mL/min) as mobile phase at 30°C. The analyte was monitored at 236 nm. No endogenous substances were found to interfere with the peaks of drug and internal standard. The value of percent deviation and the coefficient variation obtained respectively less than the percentage set in the FDA guidelines. The linearity factor values were more than 0.997 and LOD was 0.01µg/mL. UPLC with UV detector is able to analyze metformin in a short time with good precision and accuracy which is useful for bioequivalence and bioavailability studies.